The impact of stress on fertility treatment. Issue 3 (June 2016) - Rooney, Kristin L.; Domar, Alice D.
Abstract : Purpose of review: The goal of this review was to summarize the recent research on the relationship between stress and assisted reproductive technology treatment. Recent findings: Women and men with infertility report high levels of distress that can impact their quality of life. There are numerous psychosocial interventions, including cognitive behavior therapy and/or self-help ones, which may decrease distress, increase patient retention and improve pregnancy rates. Summary: Patient distress is an important factor to consider. Decreasing burden of care may lead to significant improvements in assisted reproductive technology outcome.